Implementasi Pengelolaan Keuangan Syariah Pada Pondok Pesantren Azzakariyah Di Desa Muaro Panco Kec. Renah Pembarap Kab. Merangin - Nurul Ardilah; Rafidah Rafidah; Maulana Hamzah (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
This study uses a qualitative descriptive research method, which means research whose research strategy emphasizes the decomposition of meaning, significance, concepts, characteristics, symptoms, symbols and descriptions, focus and diversity, natural and broad phenomena by prioritizing the quality of information and presenting it narratively. This research uses a phenomenological approach that seeks to capture various problems in society and reveal the meaning contained therein. The goal of qualitative research is to find out the social reality of those involved. Participants are people who have been interviewed, observed and asked for information, views and opinions. 1. This study uses a qualitative descriptive research method, which means a research whose research strategy emphasizes the decomposition of meaning, significance, concepts, characteristics, symptoms, symbols and descriptions, focus and diversity, natural and broad phenomena by prioritizing the quality of information and presenting it narratively. 2. This research uses a phenomenological approach that seeks to capture various problems in society and reveal the meaning contained therein. The goal of qualitative research is to find out the social reality of those involved. Participants are people who have been interviewed, observed and asked for information, views and opinions.